2013
DOI: 10.1590/s0036-46652013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Reference Range for T Lymphocytes Subpopulations in Adults and Children From Brazil

Abstract: SUMMARYIn Brazil, the existing reference values for T-lymphocytes subsets are based on data originated in other countries. There is no local information on normal variation for these parameters in Brazilian adults and children. We evaluated the normal variation found in blood donors from five large Brazilian cities, in different regions, and in children living in Salvador, and Rio de Janeiro. All samples were processed by flow cytometry. The results were analyzed according to region, gender, and lifestyle of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
6
17
1
2
Order By: Relevance
“…Our results show that throughout the preoperative period, nutrition and immune parameters remained stable and that after surgery there was an increase in the CD4:CD8 ratio. CD4 and CD8 levels were lower than those reported in the literature for healthy individuals (42%–44% and 24%–32%, respectively) 26 , 27 . However, our results were similar to those seen by others, such as Zhang et al, who assessed the immune profile of 82 patients with GC in different stages of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that throughout the preoperative period, nutrition and immune parameters remained stable and that after surgery there was an increase in the CD4:CD8 ratio. CD4 and CD8 levels were lower than those reported in the literature for healthy individuals (42%–44% and 24%–32%, respectively) 26 , 27 . However, our results were similar to those seen by others, such as Zhang et al, who assessed the immune profile of 82 patients with GC in different stages of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…The study confirmed the existence and general pathways of age‐related dynamic changes of main Ly subsets, earlier described for normal cohorts . Like in normal children, absolute counts of all subsets in paediatric patients gradually decreased with age.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, although different relative and absolute total Ly count in boys and girls is a well‐established phenomenon, only fragmentary and sometimes contradictory data on gender‐related variations in children have been published. Higher relative and absolute T and T4 cell counts in females of all ages were found in Brazilian population, higher T4 cell count was reported in African American and Hispanic adolescent girls in the United States; on the other hand, no statistical differences were found in an adolescent cohort from South Florida or in children born from HIV‐infected mothers …”
Section: Introductionmentioning
confidence: 80%
“…Lymphocyte subset distributions by age are reported in Table 1 (percentages) and Table 2 (absolute counts 310 9 /L), which also list WBC and lymphocyte values. We tabulated the 10th and 90th percentiles, in addition to 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) …”
Section: Resultsmentioning
confidence: 99%
“…Changes in antibody production are the hallmark of various human B-cell deficiencies, known as primary antibody deficiencies (PADs); these conditions are the most common primary immunodeficiencies (PIDs) (5). Some studies (1,2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) have demonstrated that age, sex, race, geographic area, and nutritional status can influence variation in Department of Clinical Laboratory, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, China lymphocyte subsets, and undernutrition due to insufficient intake of energy and macronutrients and/or due to deficiencies in specific micronutrients can impair the immune system, such as suppressing immune functions that are fundamental to host protection (20), which could in turn influence the distribution of different lymphocyte subsets. Normally, the immune system is functionally immature at birth, and it undergoes sequential development that is genetically determined and additionally stimulated by antigen exposure (21).…”
Section: Introductionmentioning
confidence: 99%